PENGABDIAN KEPADA MASYARAKAT TERAPI AKTIVITAS KELOMPOK STIMULASI PERSEPSI SENSORI PADA PASIEN HALUSINASI PENDENGARAN DI RUMAH SAKIT JIWA PROF.DR.MUHAMMAD ILDREM MEDAN - Gustina, Erita; Purwaningsih, Purwaningsih; Khairani, Ade Irma (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Auditory hallucinations are a condition where an individual experiences changes in the pattern and amount of stimuli internally and externally around them with reduction, exaggeration and distortion. Hallucinations are also sensory perception disorders which can be characterized by symptoms such as laughing and smiling alone, lack of concentration, movements or activities following the hallucinations. Lack of interaction with other people or the surrounding environment, and also acting like he is listening to something. Nursing actions for patients with hallucinations consist of 4 implementation strategies, namely rebuking hallucinations, conversing with other people, being able to schedule daily activities, and taking medication regularly. The aim of this community service is to provide Sensory Stimulation Group Activity Therapy to Auditory Hallucination patients at the Prof. Dr. Muhammad Ildrem Mental Hospital in Medan. This research used a total sample demonstration technique, and the sample consisted of 18 people. The results of group activity therapy activities regarding stimulation of sensory perception, auditory hallucinations by demonstration, were obtained, namely that after carrying out knowledge group activity therapy, the client's understanding was good, namely 78% and sufficient understanding, namely 22%. Therefore, it is hoped that Group Activity Therapy (TAK) is very effective in patients with auditory hallucinations.